2013
DOI: 10.1557/jmr.2013.24
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured germanium prepared via ion beam modification

Abstract: Nanostructured" germanium (Ge; also known as "voided," "porous," "nanoporous," "cratered," and "honeycomb" Ge) created via ion beam modification has been studied for many years. This work reviews the progress made in studying and characterizing the nanostructured morphology, particularly via the use of experimental techniques such as scanning electron microscopy, atomic force microscopy, and transmission electron microscopy. Specifically, the empirical observations of the structural evolution of Ge as a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 70 publications
(162 reference statements)
2
31
0
Order By: Relevance
“…However, compared to the implant damage evolution during thermal annealing and its role on dopant diffusion and activation [3][4][5][6], the as-implanted damage in Ge has received much less attention [7][8][9][10]. Relatively few studies have been performed in order to investigate the influence of the implantation parameters on the induced lattice damage.…”
mentioning
confidence: 99%
“…However, compared to the implant damage evolution during thermal annealing and its role on dopant diffusion and activation [3][4][5][6], the as-implanted damage in Ge has received much less attention [7][8][9][10]. Relatively few studies have been performed in order to investigate the influence of the implantation parameters on the induced lattice damage.…”
mentioning
confidence: 99%
“…In Ge, the material must be amorphous prior to the irradiation-induced porosity. 12 However, in TiO 2 , porosity precedes complete amorphization, which suggests that N 2 bubbles may play a crucial role in the formation of nanopores and the nanorod structure.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, for a few different types of semiconducting materials, such as indium antimonide (InSb), galliumantimonide (GaSb), and gallium nitride (GaN), ion beam modification under appropriate conditions can result in complete structural decomposition of a material to a porous microstructure consisting of nanopores. 12 Recently, Romero-Gomez et al obtained various surface nanostructures on anatase TiO 2 thin films, such as cellular defect structures or nanorod surface patterns aligned with the angle of incidence of the beam by ion irradiation. 13 However, the formation mechanism of the surface nanostructures induced by ion irradiation is still a controversial issue.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, it has been proposed in the literature to use ion beams to nanostructure several semiconductor materials such as gallium antimonide, indium antimonide, gallium nitride, and germanium. [ 22–29 ] Indeed, it is reported that these materials can become nanoporous when subjected to ion bombardment. [ 22–29 ] The use of ion beams to induce nanopores in germanium is attractive as nanoporous germanium is interesting for integration in photovoltaic cells, batteries, microelectromechanical systems or gas and bio sensors.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22–29 ] Indeed, it is reported that these materials can become nanoporous when subjected to ion bombardment. [ 22–29 ] The use of ion beams to induce nanopores in germanium is attractive as nanoporous germanium is interesting for integration in photovoltaic cells, batteries, microelectromechanical systems or gas and bio sensors. [ 22,30,31 ]…”
Section: Introductionmentioning
confidence: 99%